Cigarette smoking aggravates bleomycin-induced experimental pulmonary fibrosis. (15th March 2019) - Zhou, Li-Ling; Wang, Meng; Liu, Fei; Lu, Yu-Zhi; Song, Lin-Jie; Xiong, Liang; Xiang, Fei; He, Xin-Liang; Shuai, Shi-Yuan; Xin, Jian-Bao; Ye, Hong; Yu, Fan; et al.
Highlights: Cigarette smoking aggravates bleomycin-induced mouse pulmonary fibrosis. Cigarette smoking extract (CSE) induces collagen-I synthesis via TGF-β1-Smad2/3 and -Akt signaling. CSE induces cell proliferation via TGF-β1-Smad2/3 and -Akt signaling. TGF-β1 signaling mediates cigarette smoking aggravating pulmonary fibrosis. Abstract: Idiopathic pulmonary fibrosis (IPF) is a chronic progressive lung disease that typically leads to respiratory failure and death. The cause of IPF is poorly understood. Although several environmental and occupational factors are considered as risk factors in IPF, cigarette smoking seems to be the most strongly associated risk factor. Here firstly, we treated mice with cigarette (16 mg tar, 1.0 mg nicotine in each cigarette) smoking and tried to explore the role of cigarette smoking in pulmonary fibrosis. Mice were continuously subjected to smoke for about 1 h each day (12 cigarettes per day, 5 days per week) during 40 days. Bleomycin was administrated by intraperitoneal injection at a dose of 40 mg/kg on days 1, 5, 8, 11 and 15. We found bleomycin induced pulmonary fibrosis in mice, and cigarette smoking augmented bleomycin-induced fibrosis reflected by both in fibrotic area and percentages of collagen in the lungs. Then we prepared and employed cigarette smoke extract (CSE) in cell models and found that CSE could induce the activation of p-Smad2/3 and p-Akt, as well as collagen-I synthesis and cell proliferation in lung fibroblasts and pleural mesothelial cells (PMCs). TGF-β1 signaling mediated CSE-induced PMCs migration. Moreover, in vitro studies revealed that CSE had superimposed effect on bleomycin-induced activation of TGF-β-Smad2/3 and -Akt signaling. TGF-β-Smad2/3 and -Akt signaling were further augmented by cigarette smoking in the lung of bleomycin-treated mice. Taken together, these findings represent the first evidence that cigarette smoking aggravated bleomycin-induced pulmonary fibrosis via TGF-β1 signaling.